Exploratory analysis of circulating cytokines in patients with metastatic breast cancer treated with eribulin: the TRANSERI-GONO (Gruppo Oncologico del Nord Ovest) study. Issue 5 (13th October 2020) - Garrone, Ornella; Michelotti, Andrea; Paccagnella, Matteo; Montemurro, Filippo; Vandone, Anna Maria; Abbona, Andrea; Geuna, Elena; Vanella, Paola; De Angelis, Claudia; Lo Nigro, Cristiana; Falletta, Antonella; Crosetto, Nicola; et al.
Abstract : Background: Anticancer drugs can interact with the tumour microenvironment and their effects could be exploited to favour anticancer immune response. Eribulin contributes to tumour vasculature remodelling and transforming growth factor β (TGF-β) modulation in experimental models and in humans. We performed a prospective, translational, exploratory analysis of the levels of circulating cytokines at different time points in patients with metastatic breast cancer treated with eribulin. Methods: TGF-β, tumour necrosis factor α, vascular endothelial growth factor, IL-6, IL-8, IL-10, IL-21 and C-C motif chemokine ligand-2 levels were assessed in peripheral blood samples obtained from seven healthy volunteers and 41 patients at baseline (T0 ), after four cycles of eribulin (T1 ) and at disease progression (TPD ). Baseline values and longitudinal changes in cytokine levels were then related to clinical outcome. Results: In the 41 patients, high IL-6 and IL-8 (above the median) at T0 significantly correlated with worse survival. At T1, IL-21 significantly decreased in patients with TPD within the fourth course of treatment, compared with patients without progression. TGF-β and IL-8 above the median and IL-21 below the median at T1 significantly correlates with worse progression free survival (PFS). Patients exhibiting an increase of TGF-β or a decline of IL-21 between T0 and T1 showed a significantly worse PFS. Multivariate Cox regression analysis showed that only plasma TGF-β changes at T1 correlated with survival. At TPD, TGF-β significantly increased in all patients. Conclusions: We observed a significant correlation between TGF-β decline during eribulin treatment and outcome in patients with metastatic breast cancer. Altogether, our data suggest that eribulin treatment might interfere with the tumour microenvironment.